Online medical teaching during COVID-19: Perspectives from teachers and taught - Jyoti Rohila; Kanchan Kapoor; Jyotsna Singh; Ravi Rohilla; Palak Bansal; Palak Chhabra (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Online teaching has been practiced after lockdown due to Coronavirus Disease 2019 (COVID-19) pandemic which has replaced conventional classroom teaching. The aim of the present study was to know the perceptions regarding online learning as perceived by both teachers and students during COVID-19 pandemic. MATERIALS AND METHODS: The present study was cross-sectional and questionnaire-based. Web-based respondent-driven sampling technique was used to recruit participants for the present study. Three hundred and thirty-two students and 130 teachers of varying ages and gender participated in the study. The link of web-based questionnaire was sent to respondents through WhatsApp/Facebook. Responses from all the participants were tabulated and analyzed using univariate analysis (Chi-square test). RESULTS: Prerecorded lectures (38.9%) and Webinar apps (35/8%) were the most common modules of online teaching by students. One-third (34.3%) had the convenience to attend lectures from home whereas 44.3% had difficulty in concentration. Commonly cited disadvantage by students was inability to do practical work (37.9%). Regarding teaching faculty, 43.8% had no prior knowledge of online teaching. Sixty percent of teachers had 4 h/week of online teaching. No face-to-face interaction (67.7%) and internet issues (26.9%) were commonly stated barriers by faculty. CONCLUSION: The pandemic has pushed the teachers and students toward newer teaching avenues. However, more needs to be done to supplement the existent teaching pattern and preparedness of teaching faculty by incorporating online assignments and assessment methods, strengthening digital infrastructure in medical schools, and training support for teachers.